Current Radiology Reports - Boutin, Robert D.; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
Current Radiology Reports aims to offer expert review articles on the most significant recent developments in the field of radiology. By providing clear, insightful, balanced contributions, the journal intends to serve all those who use imaging technologies and related techniques to diagnose and treat disease. We accomplish this aim by appointing international authorities to serve as Section Editors in key subject areas across the field. Section Editors select topics for which leading experts contribute comprehensive review articles that emphasize new developments and recently published papers of major importance, highlighted by annotated reference lists. An Editorial Board of more than 20 internationally diverse members reviews the annual table of contents, ensures that topics include emerging research, and suggests topics of special importance to their country/region. Topics covered may include abdominal imaging (including virtual colonoscopy); cardiac imaging; clinical MRI; dual-source CT; interventional radiology; minimal invasive procedures and high-frequency focused ultrasound; musculoskeletal imaging; neuroimaging; nuclear medicine; pediatric imaging; PET, PET-CT, and PET-MRI; radiation exposure and reduction; translational molecular imaging; and ultrasound.
Keywords: Radiology; Imaging / Radiology